Navigated Transcranial Magnetic Stimulation Motor Mapping Usefulness in the Surgical Management of Patients Affected by Brain Tumors in Eloquent Areas: A Systematic Review and Meta-Analysis - Umana, Giuseppe Emmanuele; Scalia, Gianluca; Graziano, Francesca; Maugeri, Rosario; Alberio, Nicola; Barone, Fabio; Crea, Antonio; Fagone, Saverio; Giammalva, Giuseppe Roberto; Brunasso, Lara; Costanzo, Roberta; Paolini, Federica; et al. (Frontiers in Neurology, 2021)
Background: The surgical strategy for brain glioma has changed, shifting from tumor debulking to a more careful tumor dissection with the aim of a gross-total resection, extended beyond the contrast-enhancement MRI, including the hyperintensity on FLAIR MR images and defined as supratotal resection. It is possible to pursue this goal thanks to the refinement of several technological tools for pre and intraoperative planning including intraoperative neurophysiological monitoring (IONM), cortico-subcortical mapping, functional MRI (fMRI), navigated transcranial magnetic stimulation (nTMS), intraoperative CT or MRI (iCT, iMR), and intraoperative contrast-enhanced ultrasound. This systematic review provides an overview of the state of the art techniques in the application of nTMS and nTMS-based DTI-FT during brain tumor surgery. Materials and Methods: A systematic literature review was performed according to the PRISMA statement. The authors searched the PubMed and Scopus databases until July 2020 for published articles with the following Mesh terms: (Brain surgery OR surgery OR craniotomy) AND (brain mapping OR functional planning) AND (TMS OR transcranial magnetic stimulation OR rTMS OR repetitive transcranial stimulation). We only included studies regarding motor mapping in craniotomy for brain tumors, which reported data about CTS sparing. Results: A total of 335 published studies were identified through the PubMed and Scopus databases. After a detailed examination of these studies, 325 were excluded from our review because of a lack of data object in this search. TMS reported an accuracy range of 0.4–14.8 mm between the APB hotspot (n1/4 8) in nTMS and DES from the DES spot; nTMS influenced the surgical indications in 34.3–68.5%. Conclusion: We found that nTMS can be defined as a safe and non-invasive technique and in association with DES, fMRI, and IONM, improves brain mapping and the extent of resection favoring a better postoperative outcome.